Assessing the Association of Element Imbalances With Arsenism and the Potential Application Value of Rosa roxburghii Tratt Juice - Yuyan Xu; Baofei Sun; Qibing Zeng; Shaofeng Wei; Guanghong Yang; Aihua Zhang (Frontiers Media S.A., 2022)
Endemic arsenism caused by coal burning is a unique type of biogeochemical disease that only exists in China, and it is also a disease of element imbalances. Previous studies have shown that element imbalances are involved in the pathogenesis of arsenic; however, the interaction between the various elements and effective preventive measures have not been fully studied. This study first conducted a cross-sectional study of a total of 365 participants. The results showed that arsenic exposure can increase the content of elements (Al, As, Fe, Hg, K, and Na) in the hair (p < 0.05), but the content of other elements (Ca, Co, Cu, Mn, Mo, P, Se, Sr, V, and Zn) was significantly decreased (p < 0.05). Also, the high level of As, Fe, and Pb and the low level of Se can increase the risk of arsenism (p < 0.05). Further study found that the combined exposure of Fe-As and Pb-As can increase the risk of arsenism, but the combined exposure of Se-As can reduce the risk of arsenism (p < 0.05). In particular, a randomized, controlled, double-blind intervention study reveals that Rosa roxburghii Tratt juice (RRT) can reverse the abovementioned element imbalances (the high level of Al, As, and Fe and the low level of Cu, Mn, Se, Sr, and Zn) caused by arsenic (p < 0.05). Our study provides some limited evidence that the element imbalances (the high level of As, Fe, and Pb and the low level of Se) are the risk factors for the occurrences of arsenism. The second major finding was that RRT can regulate the element imbalances, which is expected to improve arsenism. This study provides a scientific basis for further understanding a possible traditional Chinese health food, RRT, as a more effective detoxication of arsenism.